2018
DOI: 10.21037/jtd.2018.01.86
|View full text |Cite
|
Sign up to set email alerts
|

Endobronchial treatment of peripheral tumors: ongoing development and perspectives

Abstract: Abstract:The expanded possibilities to explore the lung deeper with new tools such as electromagnetic navigation bronchoscopy (ENB) or radial probe endobronchial ultrasonography (radial EBUS), combined with miniaturization of traditional local therapies such as radiofrequency ablation (RFA), radiotherapy, cryotherapy or photodynamic therapy, let the bronchoscopists hope for new ways of endoscopic treatments.This challenge could change the practice in the upcoming decades but raise some physical and technical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Toward completion of device development and implementation, we envision deep lung catheter-based ultrasound devices ($2 mm OD) deployed through the working channel of a flexible bronchoscope, and positioned at the target site under real-time steering and guidance using CT-based electromagnetic navigation methods typical of radial endobronchial ultrasonography in peripheral lung [78]. The ultrasound ablation can be performed once the water-coupling balloon is inflated, and at completion the device can be deflated and withdrawn.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Toward completion of device development and implementation, we envision deep lung catheter-based ultrasound devices ($2 mm OD) deployed through the working channel of a flexible bronchoscope, and positioned at the target site under real-time steering and guidance using CT-based electromagnetic navigation methods typical of radial endobronchial ultrasonography in peripheral lung [78]. The ultrasound ablation can be performed once the water-coupling balloon is inflated, and at completion the device can be deflated and withdrawn.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, flexible or rigid video bronchoscopes with larger bores can facilitate placement of larger ultrasound devices (5-10 mm OD) in the larger upper airways, following similar techniques currently applied for interventions ablating obstructing tumors in the trachea and bronchus. These procedures could be via trans-nasal or oral bronchoscopic introduction, while under procedural sedation or general anesthesia, following approaches common to interventional pulmonology [78]. Post-ablation monitoring and evaluation could be performed using CT, PET, and/or MRI based imaging techniques [79].…”
Section: Discussionmentioning
confidence: 99%
“…However, in direct comparisons with SBRT in compromised patients, sublobar is consistently shown to deliver better oncological outcomes and survival, whilst causing no more morbidity . Thermal ablation of lung tumours has also been described using radiofrequency or microwave energy and can be delivered via percutaneous or endobronchial approaches . However, these have so far been performed in relatively small numbers under clinical trial settings, and it may be a number of years before sufficient data is accumulated to define their usefulness for patients.…”
Section: Is Sublobar Resection Surgery the Ideal Intervention For Ggos?mentioning
confidence: 99%
“…Note the pulmonary artery segmental branches to the target segments have been divided with vascular clips applied to the stumps (black arrow) or endobronchial approaches. 52,53 However, these have so far been performed in relatively small numbers under clinical trial settings, and it may be a number of years before sufficient data is accumulated to define their usefulness for patients.…”
Section: Is Sublobar Resection Surgery the Ideal Intervention For Gmentioning
confidence: 99%
“…Previous studies have showed that electromagnetic navigation could ease the surgeon's work, reduce complications and minimizes surgery time [9,11]. It is also used for placement of fiducial markers for stereotactic radiotherapy and accurate navigation to target lesions [12].…”
Section: Introductionmentioning
confidence: 99%